From “Land to the Tiller” to the “New Landlords”? The Debate over Vietnam’s Latest Land Reforms - Phuc To; Sango Mahanty; Andrew Wells-Dang (Land, 2019)
Between Vietnam’s independence and its reunification in 1975, the country’s socialist land tenure system was underpinned by the principle of “land to the tiller”. During this period, government redistributed land to farmers that was previously owned by landlords. The government’s “egalitarian” approach to land access was central to the mass support that it needed during the Indochinese war. Even when the 1993 Land Law transitioned agricultural land from collectivized to household holdings with 20-year land use certificates, the “land to the tiller” principle remained largely sacrosanct in state policy. Planned amendments to the current Land Law (issued in 2013), however, propose a fundamental shift from “land to the tiller” to the concentration of land by larger farming concerns, including private sector investors. This is explained as being necessary for the modernization of agricultural production. The government’s policy narrative concerning this change emphasizes the need to overcome the low productivity that arises from land fragmentation, the prevalence of unskilled labor and resource shortages among smallholders. This is contrasted with the readily available resources and capacity of the private sector, together with opportunities for improved market access and high-tech production systems, if holdings were consolidated by companies. This major proposed transition in land governance has catalyzed heated debate over the potential risks and benefits. Many perceive it as a shift from a “pro-poor” to “pro-rich” policy, or from “land to the tiller” to the establishment of a “new landlord”—with all the historical connotations that this badge invokes. Indeed, the growing level of public concern over land concentration raises potential implications for state legitimacy. This paper examines key narratives on the government-supported land concentration policy, to understand how the risks, benefits and legitimacy of the policy change are understood by different stakeholders. The paper considers how the transition could change land access and governance in Vietnam, based on early experience with the approach.